Quantum physics ≠ quantum physics. A survey of researchers' associations - Winkler, Bianca; Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2021)
No consensus has been reached so far concerning the key topics on quantum physics suitable for secondary school teaching, despite comprehensive research. We identified the the variety of associations with quantum physics among professionals as a potential cause. From an explorative mind map study with N = 29 physics researchers, we derive six subject-specific focal points in the associations that researchers have with quantum physics.<br